Numerical Simulation of Flow Behavior in an Open Channel Incoperating A Series of Groins - Jyoti, Suman; Hossain, Monir; Babu, Sumon; Bhandari, Bishnu Prasad; Ibrahim, Md. (International Journal of Scientific Research and Management (IJSRM), 2024)
Rivers in Nepal, India and Bangladesh exhibit significant instability due to their loose banks, gentle slopes at both the riverbed and water surface, and irregular sedimentation patterns resulting from substantial sediment loads originating upstream. To mitigate the impact of this instability, groins are constructed along the riverbanks to redirect the flow of water away from areas at risk. However, in numerous instances, traditional groins have proven ineffective. It is essential to conduct comprehensive studies on the performance of groins with various configurations to protect riverbanks from erosion, enhance navigation, and promote the biodiversity of aquatic species. The primary aim of this research is to simulate flow in an open channel using a series of groin models through the application of the 2D numerical model, iRIC Nays2DH. This numerical simulation employs the K-ε model for turbulence and the Cubic Interpolation Pseudo-particle (CIP) method for handling advective terms. Simulation of flow fields due to interaction of series of impermeable, permeable and combined groins placed in a straight channel has been made. A given flow condition is applied for all the groins. The simulation results depict that combined groins in series influence favorable flow fields compared to impermeable and fully permeable groins. This causes water zone near bank at the downstream of impermeable part, then slow flow through the permeable part. No strong circulation of flow at groin field and strong current after the groin head is present.